Training on Processing Chicken Feather Waste into Wall Panels as an Environmentally Friendly Alternative Material - Ansarullah Faharuddin; Muh Zainal Altim; Gusti Hardyanti Musda; Siti Aisyah (Universitas Lambung Mangkurat, 2024)
Borisallo Village is a highland area in the Parangloe sub-district, Gowa Regency, where many broiler chicken business actors have less knowledge to utilize the chicken feather waste properly, which can lead to environmental pollution. This PkM activity aims to provide education and training regarding the use and processing of chicken feather waste as an alternative material, which can be used directly by residents to improve their skills and knowledge in the use of chicken feather waste and to save the surrounding environment. The activity was held on 6-8 September 2023 in the Borisallo Village Office Yard, which was attended by around 15 participants including broiler chicken business actors, PKK members, Village officials, and members of the local Village Extension Agency. The method used was the Service Learning (SL) method, which provided the public with an understanding of the benefits of chicken feather waste based on the research results conducted previously, then held training and assistance regarding processing chicken feather waste into environmentally friendly alternative materials. The results showed that the objective of the activity was achieved in the form of increasing the knowledge and skills of the community regarding processing chicken feather waste. This can be seen from the panels made by the community had good quality according to the manufacturing procedures. The conclusion from this activity is that the community has the potential to support government programs related to Indonesia's sustainable development focus, namely the Green Economy.